Altered brain rhythms and behaviour in the accelerated ovarian failure mouse model of human menopause. Issue 4 (22nd June 2022) - Vrontou, Sophia; Bédécarrats, Alexis; Wei, Xiaofei; Ayodeji, Morikeoluwa; Brassai, Attila; Molnár, László; Mody, Istvan
Abstract: To date, potential mechanisms of menopause-related memory and cognitive deficits have not been elucidated. Therefore, we studied brain oscillations, their phase–amplitude coupling, sleep and vigilance state patterns, running wheel use and other behavioural measures in a translationally valid mouse model of menopause, the 4-vinylcyclohexene-diepoxide-induced accelerated ovarian failure. After accelerated ovarian failure, female mice show significant alterations in brain rhythms, including changes in the frequencies of θ (5–12 Hz) and γ (30–120 Hz) oscillations, a reversed phase–amplitude coupling, altered coupling of hippocampal sharp-wave ripples to medial prefrontal cortical sleep spindles and reduced δ oscillation (0.5–4 Hz) synchrony between the two regions during non-rapid eye movement sleep. In addition, we report on significant circadian variations in the frequencies of θ and γ oscillations, and massive synchronous δ oscillations during wheel running. Our results reveal novel and specific network alterations and feasible signs for diminished brain connectivity in the accelerated ovarian failure mouse model of menopause. Taken together, our results may have identified changes possibly responsible for some of the memory and cognitive deficits previously described in this model. Corresponding future studies in menopausal women could shed light on fundamental mechanisms underlying the neurological and psychiatric comorbidities present during this important transitional phase in women's lives. Abstract : Vrontou et al . report novel and specific brain rhythm alterations and signs of decreased brain regional connectivity in the accelerated ovarian failure mouse model of human menopause. These changes could be responsible for the memory and cognitive deficits previously described in this model, and ultimately, also in menopausal women. Graphical Abstract: Graphical Abstract